Advances in management accounting. 32 - Burney, Laurie L. (Advances in management accounting, 2020)
Advances in Management Accounting (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. As a premier management accounting research journal, AIMA is well-poised to meet the needs of management accounting scholars. Featured in Volume 32 are articles on: Public Sector Joint Ventures; Control; Trust; Perceived Risk; Cost Stickiness; Cost Behavior; Environmental, Social, and Governance (ESG) Sustainability Performance; Information Asymmetry; Sustainability Disclosure; Corporate Social Responsibility (CSR); Asymmetric Cost Behavior; Lease Cost Stickiness; Retail Firms Cost Stickiness; Mood; Sunshine; Managerial Optimism; Asymmetric Cost Behavior; Adjustment Costs; Academic Research, Research-Practice Gap; Rigor-Relevance; Impact; Engagement; Relational Performance Measurement System; Managerial Ability; Employee Productivity; Employee Efficiency; Employee Cost; Financial Distress; Environmental Uncertainty.- Resumé vydavatel